Epidermal features of rice leaf CV. BRRI Dhan29 (Bangladesh Journal of Plant Taxonomy, 2009)
Not available.Keywords: Leaf epidermis; Rice; Scanning electron microscopy (SEM); Slender macro hair. DOI: 10.3329/bjpt.v16i2.3931 Bangladesh J. Plant Taxon. 16(2): 177-180, 2009 (December)